Randomized Routing Algorithms for Secure Data Transmission in Wireless Sensor Networks - B, Priyanka; Mahesh, A (International Journal of Computer Sciences and Engineering, 2025)
In wireless sensor networks various security threats are encountered, so various security providing algorithms are available. Compromised node and denial of service are the two key attacks in wireless sensor networks. Here, we study routing mechanisms that circumvent black holes formed by these attacks. We argue that existing multi-path routing approaches are vulnerable to such attacks, mainly due to their deterministic nature. So once an adversary acquires the routing algorithm, it can compute the same routes know to the source, and hence endanger all information sent over these routes. We develop mechanism that generate randomized multipath routes. Under our design, the routes taken by the shares of different packets change over time. So even if the routing algorithm becomes known to the adversary, the adversary still cannot pinpoint the routes traversed by each packet. Besides randomness, the routes generated by our mechanisms are also highly dispersive and energy efficient, making them quite capable of bypassing black holes at low energy cost. Here we propose four algorithms those are purely random propagation, non-repetitive random propagation, direct random propagation and optimized random propagation and we compare the four different algorithm to study the performance. Graphical results are used to verify the effectiveness of our design.